IMPLEMENTASI KEBIJAKAN PENGEMBANGAN SARANA AIR BERSIH KAWASAN PERDESAAN DI DESA INSIL KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - LANGITAN, CHIKITA PONTICHA; LALOMA, ALDEN; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2020)
Abstract : This study aims to find out about the implementation of clean water facility developmentpolicies in rural areas in Insil Village, Passi Timur District, Bolaang Mongondow Regency. Type ofqualitative descriptive research. All data presented is in accordance with primary and secondary data.Data collection techniques based on observation, interviews and documentation. Data obtained fromvarious sources were analyzed and conclusions were drawn. The problem in this research lies in theimplementation of the policy of developing clean water facilities that have not been running optimally sothat some people still have difficulty getting clean water. The findings of this study indicate that theimplementation of clean water facility development policies in rural areas in the Insil Village of PassiTimur sub-district Bolaang Mongondow can be seen from the indicators of this research thatcommunication, resources, disposition and bureaucratic structure have not been fully implemented. Thecommunication process that occurs in the implementation of clean water facility development policies tothe lack of support by the apparatus resources in implementing clean water facility development policiescauses the implementation of these policies to not be carried out effectively. The village government needto conduct direct socializatio of programs or activities carried out related to the development of cleanwater facilities as well as improvements in coordination between relevant organizations or institutions andincrease information regarding the implementation of clean water facility development policies.Keywords : Policy Implementation, Development, Clean Water Facilities, Rural Areas.